Violent Offending Promotes Appetitive Aggression Rather than Posttraumatic Stress—A Replication Study with Burundian Ex-Combatants - Köbach, Anke; Nandi, Corina; Crombach, Anselm; Bambonyé, Manassé; Westner, Britta; Elbert, Thomas (Frontiers in Psychology, 2015)
Research has identified appetitive aggression, i.e., the perception of committed, violent acts as appealing, exciting and fascinating, as a common phenomenon within populations living in precarious and violent circumstances. Investigating demobilized soldiers in the Democratic Republic of Congo demonstrated that violent offending is associated with appetitive aggression but not necessarily with symptoms of posttraumatic stress. In the present study we sought to replicate these results in an independent and larger sample of demobilized soldiers from Burundi. As with the Congolese ex-combatants, random forest regression revealed that the number of lifetime perpetrated violent acts is the most important predictor of appetitive aggression and the number of lifetime experienced traumatic events is the main predictor for posttraumatic stress. Perpetrated violent acts with salient cues of hunting (pursuing the victim, the sight of blood, etc.) were most predictive for perceiving violent cues appealingly after demobilization. Moreover, the association of violent acts and appetitive aggression as well as traumatic events and posttraumatic stress remains strong even years after demobilization. Patterns of traumatic events and perpetrated acts as predictors for posttraumatic stress and appetitive aggression seem to be robust among different samples of ex-combatants who fought in civil wars. Psychotherapeutic interventions that address these complementary facets of combat-related disorders -- namely, posttraumatic stress and appetitive aggression -- are indispensable for a successful reintegration of those who fought in armed conflicts and to achieve a successful transition to peace.